1994
DOI: 10.1002/path.1711720110
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous T‐cell lymphoma: Clinicopathological features and prognostic parameters of 35 cases other than mycosis fungoides and cd30‐positive large cell lymphoma

Abstract: Within the group of primary cutaneous T-cell lymphomas (CTCLs), mycosis fungoides (MF), Sézary's syndrome (SS), and CD30-positive lymphomas have been delineated as clinicopathological entities. Primary CTCLs that do not belong to one of these entities represent a heterogeneous and ill-defined group of neoplasms. This paper describes the clinical and histological features of 35 of such cases. The object of this study was to define prognostic parameters for this group of primary CTCLs. Using a slightly modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
113
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 18 publications
1
113
1
1
Order By: Relevance
“…B-large cell lymphomas are mostly of follicle center cell origin and T-large cell lymphomas are classified according to the CD30 antigen expression which identify anaplastic large-cell lymphomas having a good prognosis. [3][4][5] Furthermore, these PCLL may have clinical behaviors and prognoses different from those of primary node-based malignant lymphomas of the same histologic subtype. 3,6 Treatment has not yet been well-defined, comprising radiotherapy, polychemotherapy or both, 7,8 and no prospective studies have been performed in this rare and heterogeneous group of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B-large cell lymphomas are mostly of follicle center cell origin and T-large cell lymphomas are classified according to the CD30 antigen expression which identify anaplastic large-cell lymphomas having a good prognosis. [3][4][5] Furthermore, these PCLL may have clinical behaviors and prognoses different from those of primary node-based malignant lymphomas of the same histologic subtype. 3,6 Treatment has not yet been well-defined, comprising radiotherapy, polychemotherapy or both, 7,8 and no prospective studies have been performed in this rare and heterogeneous group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…After treatment, survival rates ranged from 30 to 80% and the worst prognosis is observed in CD30 − Tlarge cell lymphomas. 5,7 For these reasons, PCLL patients included in the multicentric prospective trial of polychemotherapy (LNH87) for the treatment of aggressive lymphomas were selected and their therapeutic results, histologic features and prognostic factors for survival were analyzed. These patients were then compared to those presenting with noncutaneous lymphomas included in the same protocol and fully matched for the main clinical characteristics (age, LDH level, ECOG scale, non cutaneous extranodal site).…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: CD30-negative cutaneous large T cell lymphoma; autologous peripheral blood stem cell transplantation (APBSCT); histological transformation Cutaneous T cell lymphoma (CTCL) other than mycosis fungoides (MF) represents a rare and heterogeneous group of lymphomas; the clinical behavior has seldom been described. [1][2][3][4] In 1997, the European Organization for Research and Treatment of Cancer (EORTC) reported a new classification for primary cutaneous lymphoma. 5 In their report, CTCL were subdivided into two categories: indolent and aggressive forms according to clinical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In 1997, the European Organization for Research and Treatment of Cancer (EORTC) reported a new classification for primary cutaneous lymphoma. 5 In their report, CTCL were subdivided into two categories: indolent and aggressive forms according to clinical behavior.…”
mentioning
confidence: 99%
“…The Dutch Cutaneous Lymphoma Working Group recently published a specific classification for cutaneous T cell lymphomas (CTCL), based on both clinical and histopathological criteria. [4][5][6][7][8][9] Such classification has been recently proposed by the European Organization for Research and Treatment of Cancer (EORTC). 10 CTCL have been frequently suspected to be of viral origin.…”
Section: Introductionmentioning
confidence: 99%